Evaluation of the Levels of Evidence in Three Clinical Chapters in Five Editions of the Textbook Pathways of the Pulp - Hatami, Nima; Shahravan, Arash; Rouzpeykar, Marzieh; Nekouei, Amir Hossein; Sharifi, Maryam (Iranian Endodontic Journal, 2022)
Introduction: The levels of evidence (LOE) of dental education texts is critical from the educational point of view. The present study aimed to evaluate the levels of evidence of references used in three clinical chapters in the textbook Pathways of the Pulp. Material & Method: The references of three clinical chapters in the text book Pathways of the Pulp were assessed in five of its editions. The levels of evidence were ranked according to study type and the Oxford scale from 0 to 5. The chi-square test was used to compare the level of evidence between different editions of the "Retreatment," "Trauma," and "Surgery" chapters. Results: A total of 3656 references were reviewed and analyzed from the "Trauma" (928 references), "Re-treatment" (1906 references), and "Surgery" (822 references) chapters in the 1998, 2002, 2006, 2011, and 2016 editions. The percentage of the LOE 0 (no evidence) was high (>60%) in all three chapters in all editions (P<0.001). The levels of evidence had the same distribution in all editions (P=0.871). The LOE of the "Re-treatment" (P=0.044) and "Surgery" (P<0.001) chapters changed in some editions. Conclusion: The majority of references in the three clinical chapters of the book are low-level evidence. Encouragement policies for researchers to conduct studies with high LOE are necessary.